2015
DOI: 10.1371/journal.pone.0133293
|View full text |Cite
|
Sign up to set email alerts
|

Cat Ownership Perception and Caretaking Explored in an Internet Survey of People Associated with Cats

Abstract: People who feed cats that they do not perceive they own (sometimes called semi-owners) are thought to make a considerable contribution to unwanted cat numbers because the cats they support are generally not sterilized. Understanding people’s perception of cat ownership and the psychology underlying cat semi-ownership could inform approaches to mitigate the negative effects of cat semi-ownership. The primary aims of this study were to investigate cat ownership perception and to examine its association with huma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
72
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(77 citation statements)
references
References 36 publications
3
72
2
Order By: Relevance
“…Of all respondents, 90% answered they were strongly attached to their pet and regarded them as a family member. This is a higher proportion than in other studies of pet owners in Western countries describing a strong human-pet bond [ 18 , 19 , 20 , 21 ], and only 35–45% of respondents in one survey would have regarded their pet (dog or cat) as a family member [ 18 ]…”
Section: Discussionmentioning
confidence: 97%
“…Of all respondents, 90% answered they were strongly attached to their pet and regarded them as a family member. This is a higher proportion than in other studies of pet owners in Western countries describing a strong human-pet bond [ 18 , 19 , 20 , 21 ], and only 35–45% of respondents in one survey would have regarded their pet (dog or cat) as a family member [ 18 ]…”
Section: Discussionmentioning
confidence: 97%
“…To the best of our knowledge, there are only two empirical studies [15,28] and one review article [25] addressing this condition in cats. Studies that verify the care practices used by owners and the impacts of management on the welfare of cats are also scarce [6,12,[29][30][31].…”
Section: Introductionmentioning
confidence: 99%
“…Although support for registration and night confinement of cats is relatively high, there is nevertheless resistance to permanent confinement and bans on cat ownership (Grayson et al, 2002;Lilith et al, 2006;Travaglia & Miller, 2017). A series of studies (Toukhsati, Bennett, & Coleman, 2007;Toukhsati, Young, Bennett, & Coleman, 2012;Zito, Vankan, Bennett, Paterson, & Phillips, 2015) has additionally examined the phenomenon of cat "semi-ownership" in Australia and has sought to identify both the prevalence of this and participants' perceptions of responsibility towards semi-owned cats. This research found that although some people regularly feed cats they do not own, they are unlikely to take responsibility for neutering those animals for a number of reasons, including the assumption that other people own (and are therefore responsible for) them.…”
Section: Cat Owner Perceptions and Management Practicesmentioning
confidence: 99%